Frequency of osteoporosis in patients with peptic ulcer disease - Amber Amin; Qaisar Farooq; Jameel, Rizwan (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Peptic ulcer disease (PUD) is one of the common presentations in the medical as well as Gastroenterology clinics and it can end up in various short- and long-term complications among which osteoporosis is highly under rated. Therefore, the present study was designed to determine the frequency of osteoporosis in cases having PUD. METHODOLOGY: A cross-sectional study was conducted at the Department of Medicine during 1st January 2020 to 30th June 2020 in Sheikh Zayed Hospital, Lahore. The diagnosed cases of PUD on the basis of history and endoscopic findings with the age range of 20 to 60 years were included. Osteoporosis was labelled as yes, where a T-score of ≤ -2.5 on DEXA scan was noted. RESULTS: In this study, there were a total of 139 cases, out of which 75 (53.95%) were males and 64 (46.05%) females. The mean age of the participants was 48.11±9.43 years. Osteoporosis was observed in 14 (10.07%) out of 139 cases. Osteoporosis was seen in 05 (6.67%) males vs 09 (14.06%) females in their respective groups with p= 0.148. Osteoporosis was observed in 4 (5.80%) cases with a duration of PUD up to 2 years and 10 (14.28%) cases with duration more than this with p= 0.096. CONCLUSION: Osteoporosis is not uncommon in cases with Peptic ulcer disease, and there is no significant association with any of the confounders of this study.